Ascitic ovarian cancer is an adequate preclinical model of carcinomatosis to study intraperitoneal chemoperfusion treatment - G. S. Kireeva; O. A. Belyaeva; K. Yu. Senchik; V. G. Bespalov; A. N. Stukov; E. A. Gubareva; M. A. Maydin (Сибирский онкологический журнал)
To study the mechanisms underlying the effects of intraperitoneal chemoperfusion and to develop the optimal chemoperfusion regimen, an animal model of peritoneal carcinomatosis closely resembles a human model of peritoneal carcinomatosis is required. In our study, the model of peritoneal carcinomatosis in rats with ascitic ovarian cancer was used. material and methods. There were three groups of rats with ascitic ovarian cancer: 1 – the control group (n=15) having no treatment; 2 – rats receiving normothermic intraperitoneal chemoperfusion with cisplatin, 40 mg/kg (n=12); 3 – rats receiving hyperthermic intraperitoneal chemoperfusion with cisplatin, 20 mg/kg (n=14). All animals were euthanized with subsequent autopsy. results. Ascitic ovarian cancer developed in 100 % of the animals injected with the tumor cells. The median overall survival of rats in the control group was 9.5 days. At autopsy, all rats had ascites, and rats surviving 15‒17 days after the tumor cell injection had white tumor nodes measuring 1–3 mm in the greater omentum, intestinal mesentery, parietal and visceral peritoneum. The nodes were histologically verified as metastases of low-differentiated ovarian tumor. In 2 and 5 rats from groups 2 and 3 respectively, metastases in paratracheal lymph nodes and tumor hydrothorax were detected with no evidence of peritoneal carcinomatosis. The median survival of rats in groups 2 and 3 was significantly higher than that in the control group, being 37.5 and 25.5 months, respectively (р=0,256). conclusion. This in vivo study proved that localization of ascitic ovarian tumor, development of the tumor in all animals injected with tumor cells, fast ascites progression and peritoneal carcinomatosis make this ascitic ovarian cancer an adequate preclinical model of peritoneal carcinomatosis to study intraperitoneal chemoperfusion. Further studies are needed to understand the reasons and mechanisms of the tumor hydrothorax development in rats after intraperitoneal chemoperfusion.